2020
DOI: 10.3390/ani10112157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Zearalenone Exposure on the Growth Performance, Small Intestine Disaccharidase, and Antioxidant Activities of Weaned Gilts

Abstract: Zearalenone (ZEA) is a secondary metabolite with estrogenic effects produced by Fusarium fungi and mainly occurs as a contaminant of grains such as corn and wheat. ZEA, to which weaned gilts are extremely sensitive, is the main Fusarium toxin detected in corn–soybean meal diets. Our aim was to examine the effects of ZEA on the growth performance, intestinal disaccharidase activity, and anti-stress capacity of weaned gilts. Twenty 42-day-old healthy Duroc × Landrace × Large White weaned gilts (12.84 ± 0.26 kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…In the present study, catalase activity decreased on day 28 in the ZEN-exposed group. Similarly, Liu et al [ 86 ] also observed that exposure to ZEN at a dose of 1.04 mg·kg·feed −1 for 35 days decreased catalase activity and increased ROS production in the intestinal wall of gilts. Bellanti et al [ 87 ], Michałek et al [ 45 ] and Salah-Abbès et al [ 88 ] linked a decrease in catalase activity with oxidative stress and the depletion of defense mechanisms against ROS.…”
Section: Discussionmentioning
confidence: 82%
“…In the present study, catalase activity decreased on day 28 in the ZEN-exposed group. Similarly, Liu et al [ 86 ] also observed that exposure to ZEN at a dose of 1.04 mg·kg·feed −1 for 35 days decreased catalase activity and increased ROS production in the intestinal wall of gilts. Bellanti et al [ 87 ], Michałek et al [ 45 ] and Salah-Abbès et al [ 88 ] linked a decrease in catalase activity with oxidative stress and the depletion of defense mechanisms against ROS.…”
Section: Discussionmentioning
confidence: 82%
“…Importantly, the small intestine acts as the first line of defense for ZEA, which is mainly absorbed into the intestinal tract and can cause intestinal damage. Liu et al [ 28 ] reported that HSP70 expression and MDA content in the small intestine (duodenum, jejunum and ileum) were increased in weaned gilts fed a 1.04-mg/kg ZEA diet. The meaningful findings of this study were that ZEA might damage the intestinal structure by changing the expression of ghrelin and PCNA.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, it was hinted that 1.04-mg/kg ZEA resulted in the reduction of the functional mucosal epithelial surface area; the nutrient absorption capacity might decrease in a short time period. However, Liu et al [ 28 ] found no significant difference in the ADFI, ADG or feed efficiency (ADG/ADFI) in gilts when the gilts were treated with ZEA at 1.04 mg/kg in a diet) for 35 days. Therefore, the grow performance index was not a sensitive index of short-term intestinal injury, the morphological structure and the index of the length of the small intestine villi, and the depth of the crypts was more accurate for evaluating the effect of ZEA on the intestinal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…During the experimental period, gilts were fed a basal diet (control group) or a ZEA-contaminated diet (the basal diet supplemented with 1.0 mg/kg ZEA). Zearalenone levels used in the present study were based on our previous investigations in Shandong Province of China from 2007 to 2020 and recent literature [ 12 , 52 , 53 , 54 ]. The basal diet ( Table 3 ) used in the present study was prepared according to the NRC (2012) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…The nutrients were analyzed according to AOAC (2012) [ 56 ]. Mycotoxins were detected by the Qingdao Entry–Exit Inspection and Quarantine Bureau according to the methods of Liu et al [ 52 ], and the minimum detection concentration for ZEA, aflatoxin, fumonisin and deoxynivalenol were 0.01 mg/kg, 1.0 μg/kg, 0.1 mg/kg and 0.05 mg/kg, respectively. The analyzed ZEA contents in the basal diet and ZEA-contaminated diet were <0.01 and 1.04 ± 0.03 mg/kg, respectively, and no other toxins were detected or below the minimum detection concentration.…”
Section: Methodsmentioning
confidence: 99%